The effects of plyometric training on physical fitness and skill-related performance in female basketball players: a systematic review and meta-analysis - Cao, Shudian; Wang, Zhaoran; Guo, Jinwei; Geok, Soh Kim; Sun, He; Liu, Jia (Frontiers Media SA, 2024)
Objective: This study aims to analyze the effects of plyometric training (PT) on physical fitness and skill-related performance in female basketball players. Method: Five databases, including Web of Science, Scopus, PubMed, EBSCOhost, and Google Scholar, were used to select articles published up to 20 December 2023, using a combination of keywords related to PT and female basketball players. The risk of bias and the certainty of evidence in included articles were assessed using the Cochrane risk of bias (RoB2) tool and “The Grading of Recommendations Assessment, Development, and Evaluation” (GRADE). Results: Ten studies were included for the systematic review, and eight for the meta-analysis, totalling 246 female basketball players aged 14.5–22.5 years. Most of these players were highly trained. Most of the included studies exhibited concerns regarding the risk of bias. The PT programs lasted 4–8 weeks, conducted 2–3 sessions per week, with sessions lasting 20–90 min and including 29–190 jumps. In the systematic review, most studies showed that PT significantly improved performance in countermovement jump (CMJ), squat jump (SJ), Sargent jump, standing long jump, lateral hop, medicine ball throw, t-Test, Illinois agility, lane agility drill, linear 20-m sprint, stable and dynamic leg balance, dribbling, passing, shooting, and various basketball-specific tests, as well as increased muscle volume and thigh cross-sectional area. However, some studies showed PT to induce no significant changes in performance during CMJ, t-Test, Illinois agility, knee extensor/flexor strength, linear sprint, and single leg balance tests. In the meta-analysis, CMJ height (ES = 0.37; p = 0.036), vertical jump (VJ) peak power (ES = 0.57; p = 0.015), VJ peak velocity (ES = 0.26; p = 0.004), and t-Test performance time (ES = 0.32; p = 0.004) were significantly improved with small effects following PT. Conclusion: The effect of PT on performance in female basketball players was mixed. Most studies indicated that PT could improve various measures of physical fitness and skill-related performance, but performance remained unchanged in some tests. More studies with established tests are needed to investigate the effect of PT on female basketball players in the future.